Analysis of mRNA 3' end formation by modification interference: the only modifications which prevent processing lie in AAUAAA and the poly(A) site. - Conway, L (1987)
A modification interference method is described in which chemically modified transcripts are used to identify bases required for any reaction for which synthetic RNA is a substrate. This technique provides information analogous to that obtained from the analysis of a complete set of point mutants. Using SV40 late pre-mRNAs, we determine that modification of any base in the AAUAAA sequence prevents cleavage, polyadenylation and formation of pre-cleavage complexes in vitro. Modification of the A to which poly(A) is added prevents polyadenylation, but does not interfere with formation of the pre-cleavage complex. No single modification downstream of the poly(A) site significantly affects cleavage efficiency. Since the region downstream of the poly(A) site is required for cleavage and complex formation (Conway and Wickens, 1985; Zarkower and Wickens, 1987b), we infer that the critical features of this downstream region are either diffuse or redundant.